Assessing Swallowing of the Breastfeeding NICU Infant Using Fiberoptic Endoscopic Evaluation of Swallowing: A Feasibility Study. (June 2020) - Armstrong, Erika S.; Reynolds, Jenny; Sturdivant, Chrysty; Carroll, Sandra; Suterwala, Mustafa S.
Abstract : Background: Premature infants may demonstrate feeding difficulties requiring an instrumental swallowing assessment. Fiberoptic endoscopic evaluation of swallowing (FEES) is one assessment that can evaluate bottle feeding and breastfeeding. Purpose: This pilot study investigated the safety and feasibility of FEES for neonatal intensive care unit (NICU) infants during breastfeeding. Methods: The setting for this prospective, descriptive study was an urban level III NICU that provided care for premature and critically ill infants. Participants were 5 infants recruited from a convenience sample who were at least 37 weeks postmenstrual age, demonstrated feeding difficulties during a bedside feeding and swallowing examination, and were breastfeeding. Each participant received a FEES assessment while breastfeeding (FEES-B). Adverse events and vital signs including prefeeding and postfeeding respiratory rate, heart rate, and oxygen saturation level were recorded to assess safety. Visualization of milk, laryngeal penetration, and tracheal aspiration assessed feasibility. Results: Participants had a mean postmenstrual age of 39.8 weeks. No adverse events, including epistaxis or laryngospasm, were reported; there were no instances of autonomic instability; and there were no statistically significant differences between prefeeding and postfeeding respiratory rate, heart rate, or oxygen saturation level. Two infants successfully breastfed during FEES-B. Human milk was observable, and laryngeal penetration was noted with 1 infant. Implication for Practice: FEES-B was found to be safe, with limited data supporting feasibility. Infants demonstrated no physiologic instability during FEES-B, and milk was visualized in the pharynx during breastfeeding with 2 infants. Implication for Research: Further studies are warranted to assess effectiveness of FEES-B in infants.